Victims of age restrictions in Turkish football: a study on the social consequences of the application - Mert Zelyurt; Muazzez Sasmaz Atacocugu (Türk Spor ve Egzersiz Dergisi)
In this study, it is intended to reveal the sociological effects of "age quota rule" on Turkish football, and how football players have been affected since it was applied in the Third League in Turkey in 2008. The research method is designed as "qualitative". This method was applied as data collection tools such as questionnaire, scale, etc. in quantitative methods provide only specific options to the subjects and that creates limitations on the research problems concerning the events and processes in carrying out this method. Research data was collected through using "interview" technique, one of the most widely used method of data collection in qualitative research. Subjects are the players who cannot play in the third league due to “age quota rule". "Semi-structured in-depth interview" was conducted to 10 people. The research sample was determined by "theoretical sampling". As a result of interviews with subjects, after putting records down into paper from the voice recorder, two themes were identified based on the concepts and ideas that the subjects' narratives focused: 1 "The inability to play in the third league," 2 "The quality of football has decreased." Under the theme of "the inability to play in the third league", there are the ones who have to leave the league after the rule applied and hence join to the amateurs and the ones who cannot play in the third league due to the rule although they get best offers from the third league teams while playing at higher leagues. Another outstanding finding under this theme is the assertion that there is a fall in the wages of footballers put forward by the subjects after the quota rule applied. It is revealed that subjects' living conditions have also been affected in the negative sense and some of them state that they have some psychological problems after the rule.  Under the theme of “the quality of football has decreased" , the main reasons of quality decrease are indicated as the experienced players of older ages having to leave clubs due to the age limit and the majority of the young inexperienced players in the third league. In the current situation, that the national team squad consists of the players who come from the youth setup of big teams in the super league rather than young players is an evidence of falling short of the goal that the third league creates a source for the national team by giving more space to young players by the quota rule. Age quota restriction on the amateur football is seen as an application which does not overlap with the philosophy of amateurism and prevents people of all ages to participate in sports as a human right.